(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: The current situation of human resources and some factors related to the work motivation of health workers at Lamthao District health Center, Phutho province by 2020 ” Object and research method: Cross-sectional descriptive study, combining qualitative and quantitative research was carried out on 162 health staff at Lam Thao District health Center from January to May 2020 to describe the current situation of human resources, to determine the motivation and some factors related to the work motivation of health workers in the research area. The research results showed current situation of human resources at Lam Thao District health Center; The overall motivational factor 49% considered motivation, not motivation was 51%. Factors relationship colleagues account for the highest percentage 80% considered the driving force; The lowest is the 24% working condition factor considered as the driving force; The salary factor of 34% is considered as the motivational factor; The factor that direct managers 54% considered motivating; Factor benefits 45% as the driving force; Factor of non-material reward mechanism Factor of benefits 36% is considered as driving force; The working environment factor of 27% is considered the driving force; Factors nature of work 79% considered as motivation; Internal communication factor 71% considered the driving force. Conclusion: The current situation of human resources at the Health Center is insufficient compared with Circular 08; Some factors that strongly influence the general motivation of health workers at the Lam Thao District Health Center include: 3 social and demographic / occupational factors: age group; working time and main income in family and 06 factors of work motivation: salary factor, manager factor, non-material reward factor, working environment factor, nature factor The job and internal communication factors are related to the health workers’ general work motivation. P statistically significant <0.05.